2022
DOI: 10.1038/s41598-022-13246-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-led antimicrobial stewardship programme in a small hospital without infectious diseases physicians

Abstract: Pharmacists may be tasked to lead antibiotic stewardship programmes (ASP) implementation in small hospitals in absence of infectious diseases (ID) physicians. The objectives are to evaluate the effectiveness of a pharmacist-led ASP in a hospital without ID physician support, with special focus on indicators of the hospital use of antimicrobial agents based on consumption and asess the potential clinical and economic impact of pharmacist interventions (PIs) through the CLEO tool. A prospective quasi-experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This evidence suggests that the quality of BSI treatment can be improved by pharmacist-driven PAF, regardless of the bacterial species. It has been noted that the human resources of ID physicians are limited, and the implementation of ASPs by ID physicians universally is difficult [ 22 ]. Meanwhile, pharmacists, who have more human resources devoted to ASPs [ 23 ], are expected to be leaders in promoting ASPs.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence suggests that the quality of BSI treatment can be improved by pharmacist-driven PAF, regardless of the bacterial species. It has been noted that the human resources of ID physicians are limited, and the implementation of ASPs by ID physicians universally is difficult [ 22 ]. Meanwhile, pharmacists, who have more human resources devoted to ASPs [ 23 ], are expected to be leaders in promoting ASPs.…”
Section: Discussionmentioning
confidence: 99%
“…High acceptance rates of pharmacist recommendations by physicians were observed, demonstrating the credibility of pharmacists in ASPs [ 25 , 29 ]. Pharmacist stewardship significantly reduced overall antibiotic use, associated costs, and excessive therapy duration across various hospital departments, leading to substantive cost savings [ 20 , 28 ].…”
Section: Reviewmentioning
confidence: 99%
“…Heyerly et al [12] Reduced time to optimal antibiotics, more patients reached optimal therapy in ≤2 hours Rapid testing + pharmacist intervention improved the time to optimal antibiotics over rapid testing alone De-escalation programs led by pharmacists safely reduced the duration of antibiotic therapy and length of hospital stay without negatively impacting outcomes for gram-negative bacteremia [23], urinary tract infection [21], and other infections. Pharmacist antimicrobial stewardship (AMS) interventions reduced overall antibiotic use, costs, and therapy duration across various hospital settings, including general medicine wards [20], emergency departments [18], radiology departments [29], and small hospitals without infectious disease specialists [28]. Several studies found high acceptance rates of physician/pharmacist recommendations (Table 2) [25,29].…”
Section: First Author Main Findings Conclusionmentioning
confidence: 99%
“…Engagement of the hospital pharmacy including an understanding of antibiotic availability and consumption is essential in developing robust antimicrobial prescribing practices in the context of high AMR rates in hospital settings. Some (small) hospitals have demonstrated that, in settings where there are no infectious diseases physicians or microbiologists, pharmacist-led AMS programmes can be effective in reducing the consumption of antimicrobials and therefore retard the development of AMR (Cantudo-Cuenca et al, 2022).…”
Section: Pharmacymentioning
confidence: 99%